1971
DOI: 10.1039/j39710000275
|View full text |Cite
|
Sign up to set email alerts
|

Diels–Alder reaction of unsymmetrical dienes with methyl acrylate

Abstract: The Diels-Alder reactions of 1 -(p-substituted phenyl) buta-1.3-dienes with methyl acrylate are shown to give 2-arylcyclohex-3-enecarboxylates, irrespective of the nature of the aryl-substituent, but the steric course of the reaction is affected by the substituent. Similar results were obtained with 1 -aryl-2,3-dimethylbuta-l,3-dienes. THE Diels-Alder reaction is highly structurally specific and stere0specific.l The reaction of a l-substituted diene (1) with methyl acrylate can give rise to two structural isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Chromatography on silica gel (hexane/AcOEt = 8:3) gave 4 (4 g, 20%), 2 (2.6 g, 18%), and 3 (0.45 g, 3%). Recrystallization of 4 from ethyl acetate/hexane gave crystals: mp 165-167 °C; IR (CHC13) 1725,1675, 1620 cm-1; UV max (EtOH) 261 nm (e 3410), 295 nm (sh); UV max (EtOH-0.1 N NaOH) 308 nm (e 9600); 4H NMR (CDC13) 8 5.3 (m, 2 H), 3.7 (s, 3 H); 13C NMR (CDC13) 8 191.7 s, 183.5 s, 172.4 s, 163.1 s, 137.2 s, 136.8 s, 130.8 s, 116.0 d, 114.0 d, 65.8 s, 52.5 q, 43.4 d, 42.9 t, 42.1 d, 35.41, 34.3 t, 33.2 t, 32.3 t, 28.3 t, 27.2 t, 26.0 d, 25.81, 25.6 t, 23.8 t. Anal. Calcd for C24H2804: C, 75.76; H, 7.42.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatography on silica gel (hexane/AcOEt = 8:3) gave 4 (4 g, 20%), 2 (2.6 g, 18%), and 3 (0.45 g, 3%). Recrystallization of 4 from ethyl acetate/hexane gave crystals: mp 165-167 °C; IR (CHC13) 1725,1675, 1620 cm-1; UV max (EtOH) 261 nm (e 3410), 295 nm (sh); UV max (EtOH-0.1 N NaOH) 308 nm (e 9600); 4H NMR (CDC13) 8 5.3 (m, 2 H), 3.7 (s, 3 H); 13C NMR (CDC13) 8 191.7 s, 183.5 s, 172.4 s, 163.1 s, 137.2 s, 136.8 s, 130.8 s, 116.0 d, 114.0 d, 65.8 s, 52.5 q, 43.4 d, 42.9 t, 42.1 d, 35.41, 34.3 t, 33.2 t, 32.3 t, 28.3 t, 27.2 t, 26.0 d, 25.81, 25.6 t, 23.8 t. Anal. Calcd for C24H2804: C, 75.76; H, 7.42.…”
Section: Methodsmentioning
confidence: 99%
“…Found: C, 75.51; H, 7.59. Recrystallization of 2 from diisopropyl ether/ethyl acetate gave crystals: mp 78-80 °C; IR (CHC13) 1720,1685, 1600 cm-1; UV max (EtOH) 244 nm (e 6042); XH NMR (CDC13) 8 7.46 (dd, 1 H, J4,3 = 10 Hz, J4.5 = 6 Hz), 6.38 (d, 1 H, J3,4 = 10 Hz), 5.42 (m, 1 H), 3.8 (s, 3 H), 3.34 nm (e 3409); 4H NMR (CDC13) 8 6.44 (d, 1 H, J = 7 Hz), 6.18 (bd, 1 H, J = 7 Hz), 5.32 (m, 1 H), 3.68 (s, 3 H); 13C NMR (CDC13) 8 194.9 s, 168.3 s, 145.4 s, 141.2 s, 139.1 s, 117.2 d, 115.7 d, 115.4 d, 65.0 s, 53.1 q, 51.5 d, 35.9 t, 32.6 t, 29.6 t, 29.5 t, 26.4 t. Anal. Calcd for C16H1804: C, 70.05; H, 6.61.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it became clear that optimizing the Diels–Alder reaction of 5 with dienophiles of type 6 would not be a trivial task. For example, it has been reported that 1-aryl-1,3-butadienes and 1-aryl-2,3-dimethyl-1,3-butadienes react with methyl acrylate under thermal conditions (80–100 °C) with low to moderate endo / exo distereoselectivities, to give mixtures of the cis / trans adducts in ratios of 1.3/1 to 2.5/1 in moderate yields (50–60%) . However, to the best of our knowledge, no examples of Diels–Alder reactions between 3-methyl-1-(alkoxy/alkyl-substituted phenyl)-1,3-butadienes 5 and dienophiles 6 have been reported, except the cycloaddition reaction between diene 5d and methyl vinyl ketone 6x , which was reported to occur at high temperature (130 °C) and to give unspecified mixtures of the cis / trans cycloadducts in ratios of 2:1 and 1:6 at 130 and 200 °C, respectively…”
Section: Resultsmentioning
confidence: 97%
“…The Diels–Alder reaction between 4 and 5 is the key step of our strategy, as this allows access to a wide range of alkoxy/alkyl/halogen-substituted biaryls 7 , which are useful precursors for accessing substituted 6 H -benzo[ c ]chromen-6-ones 8 and cannabinol 3 (see Scheme ). There are relatively few examples of Diels–Alder reactions of 1-aryl-1,3-butadienes in the literature, and examples of cycloaddition reactions of dienes of type 4 with methyl propiolate ( 5 ) are particularly rare. For example, it has been reported that 4-aryl-2-silyloxybuta-1,3-dienes react with methyl propiolate ( 5 ) and other electron-deficient alkynes under thermal conditions (100 °C, for 20 h, in benzene), to give the adducts in low to moderate yields (47–64%) after acidic workup .…”
Section: Resultsmentioning
confidence: 99%